Regulatory impacts on investments by Pension Funds in Brazil - Leonardo Cardoso; João Vinícius de França Carvalho; Alexandre Teixeira Damasceno (Revista Contabilidade & Finanças, 2024)
ABSTRACT This article compares the efficient investment frontiers in light of the new standard of allocative thresholds allowed for assets guaranteeing provisions established by Resolutions of the National Monetary Council (Conselho Monetário Nacional [CMN]) Nos. 4661/2018 and 4994/2022, verifying the probability of achieving returns that cover actuarial liabilities requiring a guarantee of minimum performance. This study innovates by assessing regulatory impacts on efficient Pension Fund (Entidades Fechadas de Previdência Complementar [EFPCs]) frontiers, comparing the results of risks and viable returns obtained by the new standards, using Conditional Value-at-Risk as a coherent risk measurement, as it meets the axiom of subadditivity. Furthermore, we provide measurements of the probability of achieving specific actuarial targets and of the portfolio generating a negative result. The national supplementary pension system recently went through a crisis, related to fraud and corruption schemes in the State-owned EFPCs triggered in 2016 through Operation Greenfield. As the main response to the current context, brought by the new normative acts, risk management processes were adopted and implemented and more refined Corporate Governance mechanisms were defined in the decision-making processes related to the investment policies adopted by an EFPC. Including the flexibilization of allocative thresholds. An impact of this research is to provide theoretical support for the pension sector, in light of macroeconomic contexts possibly marked by lower interest rates, in addition to assessing the practical implications of changes proposed in the new normative resolutions. Especially because EFPCs have systemically relevant actuarial liabilities. The methodology involved conditional optimization of portfolios using Asset-Only Assets and Liabilities Management (ALM) models. Despite the flexibility of new standards, there are no differences in the returns potentially obtained, given the overlapping of efficient frontiers of models in each standard. It was found that the unrestricted model showed higher returns with substantially lower volatility when compared to restricted models, pointing out that portfolios with fewer legal constraints can generate less exposure to EFPC net worth, something extremely important for defined benefit plans.